Protein mutations following adaptation of avian influenza viruses in different biological systems. (December 2015) - Lombardo, Tina; Chiapponi, Chiara; Baioni, Laura; Cinotti, Stefano; Ferrari, Maura
Abstract: Traditionally, embryonated chicken eggs (ECE) are considered the gold standard for Influenza virus isolation and vaccine production. Nowadays, different biological systems have been improved and performed, in order to evaluate a feasible alternative to ECE. In fact, in a previous study, mammalian and avian cell cultures were successfully used for avian influenza viruses primary isolation from target tissues and virus propagation. This research is focused on the investigation of adaptive mutations that occur after influenza A virus amplification in ECE and cell cultures. The results of the study shows that avian influenza viruses after multiple passages in different biological systems undergo mutations, in particular, the largest number of amino acid substitutions occurred in all biological substrates in the hemagglutinin. Highlights: Cultivation of avian influenza A viruses (IAVs) either in ECE or established cell lines. Avian IAVs after ten passages in different biological systems undergo mutations. The largest number of amino acid substitutions occurred in the hemagglutinin. Viral propagation could result in subtypes that could differ from the wild type.